IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN FIKIH DI MI MUHAMMADIYAH PANDEAN KECAMATAN KARANGANYAR KABUPATEN NGAWI - Azharin, Barrin Putra; Khasanah, Nuthfatin Aliyatin (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2021)
This research aims to find out the implementation and factors that affect character education in Jurispruding learning in Madrasah Ibtidaiyah Muhammadiyah Pandean. This research is descriptive qualitative research. The subject of the study was 8 people, consisting of the principal, deputy head of curriculum, Jurispruding subject teacher and 5 students from 10 students in class III. Data collection techniques use interview, observation, and documentation methods. The results of character education implementation research in learning at Madrasah Ibtidaiyah Muhammadiyah Pandean include the planning and implementation of learning. At the learning planning stage the teacher lists several characters into the Learning Implementation Plan to be applied in learning. At the stage of learning the teacher internalizes character values in preliminary, core, and closing activities to develop the character of students. In the stage of learning teachers also use various methods to form the character of students, namely by using the methods of lectures, discussions, demonstrations and Q&A, and using a saintific approach so that in the learning process more emphasis on student activeness so that it is easy in the formation of student character. Factors that affect the impelementation of character education in Jurispruding learning in Madrasah Ibtidaiyah Muhammadiyah Pandean there are two factors, namely supporting factors and inhibitory factors. Supporting factors include activities applied in madrasah as a support for the success of the formation of student character and the condition of the school environment. Inhibitory factors include the timing of learning, students coming from different environments, and learning planning.